PENGUATAN KAPASITAS SUMBER DAYA MANUSIA MELALUI PELATIHAN KETERAMPILAN DIGITAL UNTUK MENINGKATKAN PRODUKTIVITAS MASYARAKAT DI CIREBON - Umi Narimawati; M. Yani Syafei; Sudadi Pranata; Amroni (Awatara Publisher, 2024)
The digital era brings new challenges and opportunities for communities, including Cirebon City, which holds significant potential in the local economic sector. This community service aims to enhance human resource capacity through digital skills training to support community productivity. The training focused on introducing basic technologies, digital marketing, and application-based financial management. The methods employed included participatory approaches through simulations, interactive discussions, and hands-on practices. The participants consisted of MSME actors, youth, and the general public who needed technological mastery in their economic activities. The results of the training showed a significant improvement in participants' understanding and application of technology. Many participants were able to utilize social media and e-commerce platforms to market their products, leading to a sales increase of up to 20%. Additionally, participants began using digital financial recording applications, making business management more efficient and accurate. However, some limitations were identified, such as the gap in technological abilities among participants and infrastructure issues in certain training locations. This program has had a wide-ranging positive impact on empowering the people of Cirebon, both in terms of enhancing technical skills and shifting mindsets. Developing more flexible modules, improving digital infrastructure, and providing continuous mentoring are necessary to ensure the long-term benefits of this training can be sustained.